ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT UPAH PEKERJA USAHA INFORMAL DI KOTA BIMA TAHUN 2023: Analysis Of Factors Affecting The Wage Level Of Informal Business Workers In Bima City In 2023 - Nurfitri, Utari; Salmah, Emi; Handayani, Tuti; Harsono, Iwan; Astuti, Endang (Ganec Swara, 2025)
The purpose of this study was to test the effect of age, working hours, education, and gender variables on the wage levels of informal business workers. The test was conducted on 70 respondents spread across three sub-districts in Bima City, namely Rasa Nae Barat, Raba, and Mpunda Districts. The method used in this study is descriptive and the data collection techniques used are questionnaires and interviews. The unit of analysis in this study is workers/laborers who work in informal businesses in Bima City. The type of data in this study is quantitative data, while the data used in this study is primary data. The sample determination was determined by purposive sampling, while the analysis used was descriptive analysis and Multiple Linear Regression Analysis along with its explanations. Based on the results of the study, it was also found that the variables of education and age had a positive but insignificant effect, indicating that workers/laborers who work in informal businesses determine the level of wages obtained not seen from the education and age of workers because in informal businesses themselves, the determination of wages is seen from the diligence and hard work done by the worker.